Oral traditions as heritage: the historiography of oral historical research on the Shona communities of Zimbabwe some methodological concerns - Mazarire, Gerald C. (Unknown, 2016)
In Zimbabwe oral historiography has been a slave to traditional political and intellectual discourses that have to a large extent dictated the manner in which the oral traditions have been collected and used. In this paper I attempt to chart the trends and the motivations behind the collection of oral traditions on and about Zimbabwe right from the first oral history collections of the Rhodesian Native Affairs Department in search for the identity of its African subjects up to those collected and interpreted by modern researchers. The paper also attempts to trace the emergence of a pool of scholars also known as antiquarians who spent a lot of time and effort collecting and publishing this oral material mostly within the context of native administration and missionary interest. It also looks at the early academic interests in oral traditions roused by anthropological research and how oral traditions came to be the focus of academic debate within successive theoretical paradigms from the nationalist discourses of the 1960s right through the various versions of Marxism. This was the point when oral traditions had become synonymous with pre-colonial history so that by the close of the 1970s there were more people working on pre-colonial topics in Zimbabwe than any other, a development that contrasts sharply with the apparent dearth in actual research on this period in the following two decades.